Light Induced Changes in Pigment and Lipid Profiles of Bryopsidales Algae - Giossi, Chiara E.; Cruz, Sónia; Rey, Felisa; Marques, Rúben; Melo, Tânia; Domingues, Maria do Rosário; Cartaxana, Paulo (Frontiers in Marine Science, 2021)
Bryopsidales (Chlorophyta) are cultured and consumed in several regions of the planet and are known for their high nutritional value and bioprospection potential, due to a high content of relevant polar lipids and polysaccharides. Among other characteristic features, these marine algae are known for possessing unique photosynthetic pigment-protein complexes and for the absence (in nearly all species investigated) of a functional xanthophyll cycle, a ubiquitous photoprotection mechanism present in most algae and plants. With the aim of characterizing the photophysiology of this atypical group of algae, we investigated the changes in pigment content and polar lipidome of two Bryopsidales species (Codium tomentosum and Bryopsis plumosa) exposed for 7 days to low or high irradiance (20 vs. 1000 µmol photons m⁻² s⁻¹). Our results show that high light has a strong effect on the pigment composition, triggering the time-dependent accumulation of all-trans-neoxanthin and violaxanthin. High light-acclimated macroalgae also displayed a shift in the characteristic polar lipidome, including a trend of accumulation of lyso-glycolipids, and highly unsaturated phospholipids and betaine lipids. We hypothesize that the observed shifts on the lipid composition could promote the interaction between all-trans-neoxanthin and violaxanthin with the siphonaxanthin-chlorophyll-protein complexes of photosystem II within the thylakoid membranes of the chloroplasts. Light induced changes in pigment and lipid composition could contribute to the fitness of Bryopsidales algae by reducing damages to the photosynthetic apparatus under increased irradiance.